Early life characteristics of capelin (Mallotus villosus) in the subarctic-arctic transition zone. (5th August 2020) - Malanski, Evandro; Munk, Peter; Swalethorp, Rasmus; Nielsen, Torkel Gissel
Abstract: Along the west coast of Greenland several fish species spawn across a wide latitudinal range encompassing significantly different environments. In an evaluation of the constraints to fish early life in high latitude ecosystems, we compared larval feeding and growth rates of an important species from the areas, the capelin ( Mallotus villosus ), at two latitudinal distant localities: the subarctic Kapisigdlit Fjord (64°25′N) and the arctic Disko Bay (69°15′N). In these areas, we describe oceanography by series of CTD casts and zooplankton and capelin larvae by fine-meshed nets. Zooplankton abundance and diversity were subsequently described and related to feeding and growth rates of the capelin larvae, assessed from analyses of larval gut contents and otolith ring-patterns. Early life characteristics of larvae differed markedly between the two areas. The onset of zooplankton production and the emergence of larvae took place earlier in Kapisigdlit than in the more northern Disko Bay. In Kapisiglit Fjord the dominant prey items for larvae were small calanoid and cyclopoid copepodites while large-sized calanoid nauplii dominated in the diet of Disko Bay larvae. Larval growth rates were lower in Kapisigdlit Fjord than in Disko Bay. We suggest that the later emergence of capelin larvae in Disko Bay could be compensated by enhanced feeding and thus growth rates, so that larvae from both populations would reach comparable sizes when entering the overwintering phase. However, while larval emergence and onset of plankton production are linked to different environmental cues (temperature increase vs light increase), a former match between emergence of larvae and preferred prey might be disrupted by the present temperature changes in the Arctic. Highlights: First comparison of early life of capelin ( Mallotus villosus ) in two latitudinal distant localities in west Greenland. Spawning was earliere in the southern locality. Different zooplankton community in the two localities. Faster larval growth rate at the northern locality. Same sizes when entering the overwintering phase.